2023
DOI: 10.3389/fbioe.2023.1142873
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effect of metal ions on the ability of Xylanase to hydrolyze wheat bran by molecular dynamics simulations

Abstract: Introduction: Wheat bran is the main by-product of wheat processing, containing about 30% pentosan and 0.4%–0.7% ferulic acid. Wheat bran is the main raw material used to prepare feruloyl oligosaccharides by hydrolysis of Xylanase, we discovered that the ability of Xylanase to hydrolyze wheat bran could be affected in the presence of different metal ions.Methods: In the present study, we have probed the effects of different metal ions on the hydrolysis activity of Xylanase on wheat bran and tried to analyze th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In previous studies, it has been reported that certain metal ions and organic reagents can enhance the activities of XYN 56,57 and FAE. 58 Therefore, in this study, we investigated the impact of additives on the activities of XYN and FAE on the P. pastoris cell surface.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In previous studies, it has been reported that certain metal ions and organic reagents can enhance the activities of XYN 56,57 and FAE. 58 Therefore, in this study, we investigated the impact of additives on the activities of XYN and FAE on the P. pastoris cell surface.…”
Section: Resultsmentioning
confidence: 98%
“…The increase in XYN activity could be due to the structural change in the active site, resulting in the enlargement of substrate-binding pocket, induced by binding with the metal ion. 57 In contrast, the introduction of ethylenediaminetetraacetate (EDTA) had an adverse effect on XYN activity, resulting in a 35% reduction at the same 5 mM concentration. Additionally, the inclusion of 2-mercaptoethanol (2-ME) and dithiothreitol (DTT) showed a slight improvement in XYN activity, with increases of 12% and 16% at the 5 mM concentration, respectively (Table 3).…”
Section: Effect Of Additives On the Enzyme Activities Of Xyn And Fae ...mentioning
confidence: 99%
See 1 more Smart Citation